2021
DOI: 10.1097/jcma.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between central serous chorioretinopathy and liver cirrhosis: A nationwide, population-based study

Abstract: Background: Central serous chorioretinopathy (CSCR) and liver cirrhosis share numerous risk factors and may have possible connections. We aimed to investigate whether patients with liver cirrhosis and the severity of cirrhosis have an increased incidence of CSCR. Methods: This population-based retrospective cohort study was conducted by collecting data from the Taiwan National Health Insurance Research Database from January 1, 2000, to December 31, 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Liver cirrhosis has been reported as an independent indicator of CSC in a population-based cohort study that reported a higher risk of CSC among cirrhotic patients with ascites and other complications. [ 136 ] Hepatic dysfunctions can modulate the plasma levels of corticosteroids. Indeed, rifampicin and ketoconazole have been used to promote the hepatic metabolism of cortisol.…”
Section: Gastrointestinal System and Central Serous Chorioretinopathymentioning
confidence: 99%
“…Liver cirrhosis has been reported as an independent indicator of CSC in a population-based cohort study that reported a higher risk of CSC among cirrhotic patients with ascites and other complications. [ 136 ] Hepatic dysfunctions can modulate the plasma levels of corticosteroids. Indeed, rifampicin and ketoconazole have been used to promote the hepatic metabolism of cortisol.…”
Section: Gastrointestinal System and Central Serous Chorioretinopathymentioning
confidence: 99%